Huge fetal hepatic Hemangioma: prenatal diagnosis on ultrasound and prognosis - Li Jiao-ling; Geng Xiu-ping; Chen Kun-shan; He Qiu-ming; Li Xiao-fen; Yang Bo-yang; Fang Qian (BMC, 2018)
Abstract Background Although huge fetal hepatic hemangiomas are rare, they can cause fatal complications. The purpose of this study is to describe the imaging features and prognosis of these tumors. Methods Imaging data were collected for 6 patients with huge fetal hepatic hemangiomas treated at our hospital. Imaging modalities included prenatal magnetic resonance imaging and ultrasound and postnatal color Doppler ultrasound and contrast-enhanced computed tomography (CT). Results Among the 93,562 fetuses of 92,126 pregnant women examined at our hospital, 6 had huge hepatic hemangiomas (incidence rate, 0.64/10,000), as confirmed via postnatal color Doppler imaging and contrast-enhanced CT. Five fetuses had solitary lesions, whereas 1 (fetus 2) had multiple lesions. Four fetuses had lesions in the right liver lobe and 1 had a lesion in the left liver lobe, and 1 (fetus 2) had lesions in both lobes. All lesions showed centripetal enhancement on postnatal contrast-enhanced CT, which was more intense peripherally. Following postnatal treatment with oral propranolol, with or without dexamethasone or interventional therapy with the medical sclerosant pingyangmycin, all lesions decreased in size, with calcification plaques appearing 6 months after treatment. Conclusions Huge hepatic hemangiomas have typical ultrasonographic features and can be diagnosed prenatally. Treatment with propranolol, with or without dexamethasone, may result in a favorable prognosis.